12th Conference on Transcription and Chromatin - August 27-30, 2016 - Heidelberg, Germany. Issue 11 (1st November 2016) - Duttke, Sascha H. C.
ABSTRACT: A pleasant atmosphere and outstanding science certainly made the 12th EMBL Conference on Transcription and Chromatin an event to remember. With 62 talks and over 200 posters, there was no shortage of cutting edge research to catch on.